Kritik Sosial Pers terhadap Penanganan Kasus Korupsi di Indonesia - Benar Kondang Wijaksono; Eka Nada Shofa Alkhajar (Universitas Sebelas Maret (UNS), 2026)
Editorial is a main article that reflects the views and opinions of a newspaper. Newspapers as the press can write social criticism regarding an issue to carry out its normative function as a tool of social control. Using the perspective of (Abar, 1997), this study analyzes the findings of social criticism in the editorial text of the print newspaper Media Indonesia. The main focus of the analysis is social criticism related to the handling of corruption cases in Indonesia. Handling corruption cases includes prevention, disclosure of cases, and prosecution or law enforcement. In its aim to find social criticism regarding the handling of corruption cases in Indonesia, the research method used is qualitative content analysis. By collecting data through observation and documentation of editorial texts by Media Indonesia at the National Press Monument. Researchers continued to take samples using the purposive sampling method. This research captures that: (1) Indonesian media pays attention to the handling of corruption cases in Indonesia. This attention is shown by the social criticism related to this matter written in the editorial text. (2) Indonesian media conveys social criticism accompanied by arguments and solutions. Social criticism is not written directly and avoids conflict with the government so it is included in the middle way model.